Royal College of Nursing (Rcn) code of professional conduct: a discussion document. Issue 3 (September 1977) - Dawson, J D; Altschul, A T; Sampson, C; Smith, A M
Abstract : We are printing in its entirety the discussion document which sets out a code of professional conduct for nurses published by the Royal College of Nursing in November 1976 together with commentaries by the Assistant Secretary of the British Medical Association, a professor of nursing studies, student nurses and a lawyer. The image of the nurse is still that of one of Florence Nightingale's young ladies or of a member of a religious order who is wholly dedicated to caring for the sick. Today, as this document and the comments upon it show, 'dedication' is still part of the motive which leads a man or woman to become a nurse but in addition, and this is where the public may be ignorant or choose to be ignorant, nursing offers a career where intellectual achievement and the satisfaction of a demanding job bring their proper financial reward and place in the professional community. We are grateful to the Royal College of Nursing for permission to publish this document.